2017
DOI: 10.1371/journal.pone.0186609
|View full text |Cite
|
Sign up to set email alerts
|

Association between a miRNA-146a polymorphism and susceptibility to head and neck squamous cell carcinoma in Chinese patients: A meta-analysis of 8 case–control studies

Abstract: A closer association has been found between the microRNA-146a rs2910164 polymorphism and the risk of head and neck carcinoma in some molecular epidemiological studies. Recently two meta-analyses were performed to explore the relationship between miRNA-146a polymorphisms and the susceptibility of squamous cell carcinoma of the head and neck (SCCHN); however, they yielded conflicting results in susceptibility regarding ethnic variations. Hence, the present study was performed to explain the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…We found that patients with CASP9 c.‐1339GG genotype had worse EFS than others. In disagreement with our data, the G allele or GG genotype was previously associated with increased survival in bladder, 4 colorectal, 2 and gastric 6 cancer patients, and did not alter survival in patients with lung 5 and hepatocellular 8 cancer. Since higher mRNA levels, suggesting a higher transcriptional activity, were previously associated with the G allele of CASP9 c.‐1339A>G SNV, 2 our data were not expected.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that patients with CASP9 c.‐1339GG genotype had worse EFS than others. In disagreement with our data, the G allele or GG genotype was previously associated with increased survival in bladder, 4 colorectal, 2 and gastric 6 cancer patients, and did not alter survival in patients with lung 5 and hepatocellular 8 cancer. Since higher mRNA levels, suggesting a higher transcriptional activity, were previously associated with the G allele of CASP9 c.‐1339A>G SNV, 2 our data were not expected.…”
Section: Discussioncontrasting
confidence: 99%
“…Rs2910164 was not only the most studied miRNAs-SNP in CRC but it was also well investigated in other different cancers. The meta-analyses from the last few years demonstrated the association of rs2910164 with the increased risk of lung cancer [ 118 , 119 ], head and neck carcinoma [ 120 ], urological neoplasms, particularly bladder cancer [ 121 ], gastric cancer [ 35 ] and brain tumors [ 122 ]. For the last two cancers this risk was linked to GG genotype.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-146a was validated extensively in our study and is the only microRNA that has been described in oral cancer and potentially malignant oral disorders in both complete genome and candidate gene studies (17,20,21). Its implication in inflammatory and immunological processes, as well as in various neoplasms including oral cancer, has been demonstrated (21-25). Recently, Zhang et al (25) demonstrated that the allelic variants of miR-146a rs2910164 in a Chinese population may be associated with a higher risk of presenting head and neck squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Its implication in inflammatory and immunological processes, as well as in various neoplasms including oral cancer, has been demonstrated (21-25). Recently, Zhang et al (25) demonstrated that the allelic variants of miR-146a rs2910164 in a Chinese population may be associated with a higher risk of presenting head and neck squamous cell carcinoma. Based on these findings, we consider that microRNA-146a may be an important element in oral carcinogenesis by mediating the regulation of the proinflammatory pathways with a carcinogenic potential (26).…”
Section: Discussionmentioning
confidence: 99%